Antena Discreta com Patch Circular Confeccionada Sobre Substrato Dielétrico Cerâmico à Base de Pentóxido de Nióbio Nb2O5 - Silveira, Jorge Henrique de Almeida (Universidade Federal Rural do Semi-Árido, 2015)
The microstrip antennas are the most versatile and used in microwave antennas, is constituted by a metal element and a radiator planeseparated by a dielectric material, called substrate in the technical literature. This work has as main goal to build a microstrip antenna with Patch in circular format, using as material for making the dielectric substrate Niobium pentoxide (Nb 2O5). Thus, there has been a dielectric base substrate making use of this material for both the powder metallurgy method, which comprises three stages namely milling, compression or compaction and sintering. The substrate produced was characterized electrically and showed a low permittivity and low loss tangent for a frequency range in 8,2GHz microwave to 12,4GHz. The microstrip antenna made from this substrate is designed to resonate at a frequency around 10 GHz by the cavity method. The numerical results obtained in the simulations, and measurements made with the antenna were satisfactory and with good agreement
Discrete Patch Antenna with Circular Made Dielectric ceramic substrate on the basis of Niobium pentoxide - Nb2O5
Keywords: Antennas; Niobium pentoxide; Wireless communication systems; Antenas; Pentóxido de nióbio; Sistemas de comunicação sem fio; ENGENHARIAS::ENGENHARIA ELETRICA